A study on the relationships between different presentation modes of graphical icons and users' attention. (October 2016) - Lin, Hsuan; Hsieh, Yu-Chen; Wu, Fong-Gong
Abstract: With the vigorous development of applications (App), graphical user interfaces (GUI) have been widely found in computers and handheld devices. This study aimed to explore the relationships between different presentation modes of graphical icons and users' attention. An eye tracker was employed to measure each participant's experimental data; in addition, subjective evaluation of attention was conducted. Thus, the optimum presentation mode attracting the most attention might be determined. The experiment was designed to investigate two variables: icon composition and background. Through permutation and combination, six presentation modes were obtained as follows: line + positive background (M1), plane + positive background (M2), line + negative background (M3), plane + negative background (M4), line + no background (M5), and plane + no background (M6). Thirty-six participants were requested to view thirty stimuli, or the contour drawings of graphical icons, presented simultaneously in six modes mentioned above. The participants' fixation duration, fixation frequency, and subjective evaluation of attention were analyzed through two-way ANOVA. The analytical results showed that in terms of the three performance indicators above, M4 performed the best among the six presentation modes. Moreover, regarding icon composition, planes performed better than lines in terms of the three performance indicators. As for background, negative background performed the best in terms of the three performance indicators, positive background ranked second, and no background performed the worst. The findings can serve as a reference when icons are researched or designed in the future. Highlights: Icon composition and background have a statistically significant effect on fixation duration. The icon composed of plane + negative background performs the best, attracting the greatest amount of attention. Planes perform better than lines in terms of fixation duration, fixation frequency, and subjective evaluation of attention. Negative background performs better than positive background, and positive background performs better than no background.